2021
DOI: 10.3390/jcm10061181
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Perceived Access to Care among People Who Inject Drugs in Athens, Greece

Abstract: Poor mental health among human immunodeficiency virus (HIV)-positive people who inject drugs (PWID) may contribute to stigma, and together they act as barriers to medical care. This analysis aims to examine factors associated with the mental health of PWID and their network contacts, and the association of poor mental health with the experience of HIV-related stigmatizing events, with HIV-related social support, and with perceived access to care. Data were collected during the Transmission Reduction Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…These contacts were then recruited and asked to identify, in turn, their sexual and drug-use partners, who were also recruited, and their connections to other individuals in the study were ascertained. If any of these partners were identified as recently infected with HIV, then their contacts and the contacts of their contacts (i.e., two waves of contact tracing) would be recruited as well, and their contacts were ascertained [ 146 ]. In addition, longer-term HIV-infected individuals (long-term control seeds) were also recruited, and their network contacts were traced based on the same procedure described above.…”
Section: Illustrative Example: the Transmission Reduction Interventio...mentioning
confidence: 99%
See 1 more Smart Citation
“…These contacts were then recruited and asked to identify, in turn, their sexual and drug-use partners, who were also recruited, and their connections to other individuals in the study were ascertained. If any of these partners were identified as recently infected with HIV, then their contacts and the contacts of their contacts (i.e., two waves of contact tracing) would be recruited as well, and their contacts were ascertained [ 146 ]. In addition, longer-term HIV-infected individuals (long-term control seeds) were also recruited, and their network contacts were traced based on the same procedure described above.…”
Section: Illustrative Example: the Transmission Reduction Interventio...mentioning
confidence: 99%
“…Moreover, the TRIP staff, using a combination of approaches to improve case management (information and instrumental support, multiple reminders, multiple and consistent efforts to overcome administrative obstacles), was achieved to connect almost 87% of the recently HIV-infected PWID participants into care; 77% of those began antiretroviral treatment, and eventually 89% had very low viral load levels [ 147 ]. The data analyses also showed that the behavioral patterns reported by the participants at the follow-up interview of TRIP were much safer than those reported at the start of the project [ 148 ], while the project was not associated with any adverse events in terms of the mental health of the participants or any TRIP-related stigmatizing experiences [ 146 , 149 ]. Instead, there was some evidence that HIV-related support increased significantly over the course of the project [ 149 ].…”
Section: Illustrative Example: the Transmission Reduction Interventio...mentioning
confidence: 99%